ANALISIS PEMANFAATAN APLIKASI PLATFORM MERDEKA MENGAJAR (PMM) BAGI GURU SEKOLAH DASAR - Puspitasari, Lintang; Zumrotun, Erna (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
This research aims to analyze the use of the Merdeka Mengajar Platform application by teachers at SDN 4 Jambu. A descriptive qualitative approach was used to describe the use of the PMM application. The research subjects consisted of 6 teachers who taught in grades 1 to 6 at SDN 4 Jambu, and was carried out on 20-22 May 2024. Data was collected through observation, interviews and documentation analysis. The research results show that the Merdeka Mengajar Platform has a positive impact on teachers in particular. The government has provided an account that teachers can use to access the Merdeka Mengajar Platform application for free. The platform design makes it easy for teachers to use features such as independent training, student assessments, real actions, communities, and inspirational videos that help plan and implement learning. Teachers at SD Negeri 4 Jambu responded positively to the usefulness of this platform, which significantly improved the quality of learning.